2018
DOI: 10.1093/aob/mcy180
|View full text |Cite
|
Sign up to set email alerts
|

Auxin transport and stem vascular reconnection – has our thinking become canalized?

Abstract: Background The presence of a polar auxin transport stream has long been correlated with the differentiation and patterning of vascular cells across vascular plants. As our understanding of auxin transport and vascular development has grown, so too has evidence for the correlation between these processes. However, a clear understanding of the cellular and molecular mechanisms driving this correlation has not been elucidated.• Scope This article examines the hypothesis that canalization via polar auxin transport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 90 publications
(107 reference statements)
0
23
0
Order By: Relevance
“…Until recently, it was thought that through polarization of PIN1 auxin transport proteins, plants re‐establish polar auxin transport (PAT) between the scion and rootstock across the graft junction and these cell files then undergo differentiation to reconnect the vasculature (Sawchuk and Scarpella 2013, Wang et al 2017). However, recent auxin transport studies by Wulf et al (2019) using the radiolabeled auxin [ 3 H]‐indole‐3‐acetic acid have questioned this canalization hypothesis. It was demonstrated that despite a significant disruption to PAT in interspecies grafts, no difference in the number of vascular cells reconnecting scion to rootstock could be seen (Wulf et al 2019).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Until recently, it was thought that through polarization of PIN1 auxin transport proteins, plants re‐establish polar auxin transport (PAT) between the scion and rootstock across the graft junction and these cell files then undergo differentiation to reconnect the vasculature (Sawchuk and Scarpella 2013, Wang et al 2017). However, recent auxin transport studies by Wulf et al (2019) using the radiolabeled auxin [ 3 H]‐indole‐3‐acetic acid have questioned this canalization hypothesis. It was demonstrated that despite a significant disruption to PAT in interspecies grafts, no difference in the number of vascular cells reconnecting scion to rootstock could be seen (Wulf et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…However, recent auxin transport studies by Wulf et al (2019) using the radiolabeled auxin [ 3 H]‐indole‐3‐acetic acid have questioned this canalization hypothesis. It was demonstrated that despite a significant disruption to PAT in interspecies grafts, no difference in the number of vascular cells reconnecting scion to rootstock could be seen (Wulf et al 2019). Additionally, grafting experiments using auxin transport and biosynthesis mutants showed no obvious defects in the formation of new vascular connections (Melnyk et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations